2023
DOI: 10.1177/09514848231151814
|View full text |Cite
|
Sign up to set email alerts
|

High-cost drugs for rare diseases: their expenditure and value based on a regional area-based study

Abstract: Background: in the field of rare diseases (RDs) most of the European studies on budget impact analysis of drugs that have been conducted often lay on theoretical assumptions and focus only on Orphan drugs (ODs). Objectives: we aimed to estimate the budget impact of specific drugs for non-oncological RDs, both ODs and non-ODs, using real-world data about patients residing in Veneto Region (Italy) and to describe its expenditure structure and dynamics. Methods: a population-based multi-source observational study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Frontiers in Pharmacology frontiersin.org overpriced (Manea et al, 2023). Our study also revealed that drugs for severe diseases and those without alternatives had higher annual treatment costs and a higher price ratio to the A7 average adjusted price.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Frontiers in Pharmacology frontiersin.org overpriced (Manea et al, 2023). Our study also revealed that drugs for severe diseases and those without alternatives had higher annual treatment costs and a higher price ratio to the A7 average adjusted price.…”
Section: Discussionsupporting
confidence: 53%
“…Treatments for rare diseases are concentrated around metabolic and hematological diseases, raising concerns about other rare diseases that are therapeutically neglected. Drugs for diseases lacking adequate treatment options with a high societal demand for the same tend to be overpriced ( Manea et al, 2023 ). Our study also revealed that drugs for severe diseases and those without alternatives had higher annual treatment costs and a higher price ratio to the A7 average adjusted price.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone pain of varying intensity, fractures, and progressive joint collapses may cause impaired mobility and increased morbidity [ 5 ]. To date, the management of bone pathology remains challenging even after the introduction of specific disease-modifying therapies such as enzyme replacement therapy (ERT: imiglucerase, velaglucerase alfa, and taliglucerase) or substrate reduction therapy (SRT: eliglustat and miglustat) [ 6 ], which have a high economic impact on the health system [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%